Zolmitriptan Mouth Dissolving Tablets: Development of Formulas and Invitro Evaluation - Uzma Fatima; K.Yadava Reddy (Emerging Trends in Personalized Medicines, 2024)
Pharma Burst ODT super disintegrants were used in different concentrations to manufacture Zolmitriptan fast dissolving tablets by a direct compression method. With a 28° angle of repose, there is good flow. The densities for bulk and tapped materials are 0.410 (g/ml) and 0.500 (g/ml), respectively. The compressibility index and Hausner ratio have values of 19.05 and 1.24, correspondingly. According to IP standard, weight variation test results range from 121.4 mg to 126.1 mg. Friability: Less than 0.31%, according to the data, means that the percentage losses did not exceed 1.0% (complies with IP requirements). The thickness of the tablets ranges from 2.90 mm to 2.99 mm. Based on the results, it can be packed. There was a range of 98.62% to 100.3% content homogeneity. It was discovered that the tablet's hardness ranged from 4 to 4.6 kg/cm2. The outcomes show that the tablets are within limit and have a solid mechanical structure. The disintegration time of the pills was found to be within a 30-second range, ranging from 0'11 to 0'16 seconds. For formulations FZ1, FZ2, FZ3, ZF4, FZ5, ZF6, FZ7, FZ8, and FZ9, a dissolution investigation was conducted in 6.8 pH phosphate buffer between 0 and 15 minutes. For formulations FZ9 and commercial product, a comparative dissolving analysis was conducted in phosphate buffer with a pH of 6.8. Tablet storage conditions: For 0, 30, 60, and 90 days, tablets were kept at 45°C ± 2°C/75%. The hardness of the tablets was gradually increased over time, but it was always within the permissible range. Disintegration time: varies depending on storage circumstances, but never exceeds 20 seconds, or less than 30 seconds (IP standard). The dissolving data of the formulations both at the beginning and after the designated storage period did not significantly alter, according to dissolution studies.
Keywords: Direct compression method; Disintegration time; Dissolution studies; Fast dissolving tablets; Zolmitriptan